Land rights, agricultural productivity, and deforestation in Viet Nam - Ryan Abman; Conor Carney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper studies the relationship between land tenure for smallholder agriculture and deforestation in Viet Nam. We combine high resolution satellite data on deforestation with rich household and commune-level, biannual panel data. We study two margins of tenure security, whether a household has any land title (extensive) and the share of a household's land held in title (intensive). Using a household-fixed effects model, we find the increases in crop production and land investment associated with holding land title are driven by the intensive margin. We then aggregate the survey data to the commune-level and find evidence that marginal increases in extensive tenure (share of households with any land title) increase deforestation holding constant the average intensive tenure (average share of land held in tenure among those with land title). We find some evidence that increasing the intensive margin of tenure (holding constant the extensive tenure) decreases deforestation. These results present a more nuanced view of the tenuredeforestation relationship than is prevalent in the existing literature.
Keywords: Q15; Q23; O13; 330; Deforestation; agricultural productivity; land tenure; Viet Nam